Effects of large herbivores on fire regimes and wildfire mitigation. Issue 12 (5th September 2021) - Rouet‐Leduc, Julia; Pe'er, Guy; Moreira, Francisco; Bonn, Aletta; Helmer, Wouter; Shahsavan Zadeh, Shahin A. A.; Zizka, Alexander; van der Plas, Fons
Abstract: Abandonment of agricultural land is widespread in many parts of the world, leading to shrub and tree encroachment. The increase of flammable plant biomass, that is, fuel load, increases the risk and intensity of wildfires. Fuel reduction by herbivores is a promising management strategy to avoid fuel build‐up and mitigate wildfires. However, their effectiveness in mitigating wildfire damage may depend on a range of factors, including herbivore type, population density and feeding patterns. Here, we review the evidence on whether management with herbivores can reduce fuel load and mitigate wildfires, and if so, how to identify suitable management that can achieve fire mitigation objectives while providing other ecosystem services. We systematically reviewed studies that investigated links between herbivores, fire hazard, fire frequency and fire damage. We found that, in general, herbivores reduce fuel load most effectively when they are mixed feeders, when grazing and browsing herbivores are combined and when herbivore food preferences match the local vegetation. In some cases, the combination of herbivory with other management strategies, such as mechanical clearing, is necessary to reduce wildfire damage. Synthesis and Applications . We conclude that herbivores have the capacity to mitigate wildfire damage, and we provide guidance for grazing management for wildfire mitigation strategies. As areas undergoing land abandonment are particularly prone to wildfires, the maintenance or promotion of grazing by domestic or wild herbivores is a promising tool to reduce wildfire risk in a cost‐effective way, while also providing other ecosystem services. Relevant land‐use policies, including fire suppression policies, agricultural and forest(ry) policies could incentivise the use of herbivores for better wildfire prevention. Abstract : We conclude that herbivores have the capacity to mitigate wildfire damage, and we provide guidance for grazing management for wildfire mitigation strategies. As areas undergoing land abandonment are particularly prone to wildfires, the maintenance or promotion of grazing by domestic or wild herbivores is a promising tool to reduce wildfire risk in a cost‐effective way, while also providing other ecosystem services. Relevant land‐use policies, including fire suppression policies, agricultural and forest(ry) policies could incentivise the use of herbivores for better wildfire prevention. Abstrait: La déprise rurale est omniprésente dans de nombreuses régions du monde, ce qui entraîne notamment un embroussaillement généralisé des terres agricoles. L'augmentation de la biomasse végétale inflammable, c'est‐à‐dire de la charge en combustible, accroît le risque et l'intensité des incendies de forêt. L'utilisation de grands herbivores ongulés pour la gestion du combustible est une stratégie prometteuse pour éviter l'accumulation de combustible et atténuer les incendies de forêt. Toutefois, leur efficacité à limiter les dommages causés par les incendies de forêt peut dépendre d'une série de facteurs, notamment la densité de pâturage, le type d'herbivore et les habitudes alimentaires de ces derniers. Nous examinons ici si la gestion du combustible par le pâturage permet de prévenir et atténuer les feux de forêt et, le cas échéant, comment les prévenir et les atténuer tout en fournissant d'autres services écosystémiques. Nous avons examiné de manière systématique la littérature scientifique existante sur les liens entre les herbivores, le risque d'incendie, la fréquence des incendies et les dommages causés par les incendies. Nous avons constaté qu'en général, les herbivores réduisent la charge de combustible de la manière la plus efficace lorsque les préférences alimentaires des herbivores sont adaptées à la végétation locale. Dans certains cas, la combinaison du pâturage avec d'autres stratégies, telles que le débroussaillage, est nécessaire pour la prévention des feux de forêt. Synthèse et applications . Nous concluons que le pâturage a la capacité d'atténuer les dommages causés par les feux de forêt, et nous fournissons des recommandations pour la gestion du pâturage dans le cadre de stratégies d'atténuation des incendies de forêt. Les zones en cours d'abandon étant particulièrement exposées aux incendies de forêt, le maintien ou la promotion du pâturage par des herbivores domestiques ou sauvages est un outil prometteur pour réduire le risque d'incendie de forêt de manière rentable, tout en fournissant d'autres services écosystémiques. Les politiques publiques en matière d'aménagement du territoire, notamment les politiques de lutte contre les incendies ainsi que les politiques agricoles et forestières pourraient encourager l'utilisation d'herbivores pour une meilleure prévention des incendies. Abstract: Het verlaten van marginale landbouwgronden door jongere generaties komt overal op de wereld voor en leidt vaak tot verbossing en verstruiking van het landschap. De toename van biomassa, in combinatie met verdichting van de vegetatie, verhoogt de kans op grootschalige natuurbranden. Een veelbelovende oplossing is het inzetten van grote herbivoren, om de productie van vegetatieve brandstoffen te beperken. Echter, de effectiviteit van herbivoren in het reduceren van natuurbranden hangt van verscheidene factoren af, waaronder de soortensamenstelling, de populatiedichtheid en het dieet van de herbivoren. In dit overzichtsartikel bespreken we in hoeverre bestaand onderzoek laat zien dat begrazingsbeheer natuurbranden kan reduceren. Daarnaast identificeren we welk beheer zowel effectief is in het reduceren van natuurbranden, alsmede in het leveren van andere ecosysteem diensten. Daarvoor hebben we systematisch studies met elkaar vergeleken, die verbanden tussen herbivoren, vegetatiestructuur, de frequentie van natuurbranden en de intensiteit van natuurbranden onderzochten. We ontdekten dat over het algemeen herbivoren het meest effectief zijn in het reduceren van de hoeveelheid brandstoffen als ze naast gras ook andere planten zoals struiken eten, als herbivoren met verschillende dieetkeuzen samen in een gebied voorkomen en als de dieetvoorkeuren van herbivoren goed aansluiten op de voedselbeschikbaarheid in hun omgeving. In sommige gevallen blijft het nodig om begrazing te combineren met andere beheersmaatregelen, zoals het lokaal, mechanisch verwijderen van vegetatie. Synthese en toepassingen . we concluderen dat herbivoren de schade van natuurbranden kunnen reduceren, en we stellen strategieën voor om dit doel te bereiken. Deze kunnen met name interessant zijn voor gebieden die te maken hebben met ontvolking en daardoor een toegenomen frequentie en schaal van natuurbranden. Hier kan begrazing door gedomesticeerde of wilde herbivoren zeer (kosten‐) effectief zijn en daarnaast ook andere ecosysteemdiensten faciliteren. Door hun beleid ten aanzien van landbouw, bosbouw en brandbestrijding hierop aan te passen, kunnen overheden een belangrijke rol spelen bij het stimuleren van herbivorie als effectief middel ter bestrijding van grootschalige natuurbranden.